The Linguistic and Grammatical Foundations for Understanding Prophetic Hadith Texts: Proposed Strategies and Mechanisms/ الأسس اللغوية والنحوية لفهم نصوص الحديث النبوي: استراتيجيات وآليات مقترحة - Abdelhamid, Ibrahim Youssef; Othman, Mohamed Ibrahim Hassan; Othman, Abdel Sattar Abd Elwahab Ayoub; Mohammad Nazmi, Mohamad Zhafri; Yahaya, Hazrati; Abas, Ummu-Hani Binti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Understanding the secrets of language and the methods used by Arabs in their speech helps comprehend the intended meaning of the Prophet's words: peace be upon him. This research aims to develop a conceptual framework and proposed strategies and mechanisms for understanding the Prophetic Tradition based on linguistic knowledge. It also seeks to demonstrate the role of the objectives of Arabic grammar in understanding the Prophetic Tradition and introduce modern grammatical theories and their role in understanding the Prophetic Tradition. The research adopted a descriptive-analytical approach, and its findings indicate that understanding the objectives of Arabic grammar assists in comprehending many problematic aspects found in some narrations. The results: the lack of knowledge of the external context of a hadith leads to misconceptions, and the theory of textual grammar contributes to understanding the meanings of the Prophetic Tradition. The indirect style in language also aids in identifying the purpose and intent of the Prophetic Tradition. The researchers recommend conducting serious linguistic studies on linguistic expression and meaning, examining their characteristics and roles in elucidating the legal objectives of the Prophetic text, as they are essential in deducing juristic rulings.